2020
DOI: 10.1038/s41467-020-16931-0
|View full text |Cite
|
Sign up to set email alerts
|

Remote assessment of the fate of phytoplankton in the Southern Ocean sea-ice zone

Abstract: In the Southern Ocean, large-scale phytoplankton blooms occur in open water and the sea-ice zone (SIZ). These blooms have a range of fates including physical advection, downward carbon export, or grazing. Here, we determine the magnitude, timing and spatial trends of the biogeochemical (export) and ecological (foodwebs) fates of phytoplankton, based on seven BGC-Argo floats spanning three years across the SIZ. We calculate loss terms using the production of chlorophyll-based on nitrate depletion-compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 71 publications
0
52
0
Order By: Relevance
“…In the Weddell Gyre, for example, microzooplankton grazing is a major controlling factor and more important than larger zooplankton, while viral infections are suggested to be of less importance (reviewed in Vernet et al, 2019). Regarding total losses, a recent study partly concerning our study area and based on bio-optical observations from BGC-Argo floats, concluded that grazing (including viral lysis) was responsible for 83% of the losses on average and was by far more important than phytodetritus sinking (Moreau et al, 2020). In addition, grazing was found to be more important in the later part of the production season.…”
Section: Bloom Endmentioning
confidence: 88%
“…In the Weddell Gyre, for example, microzooplankton grazing is a major controlling factor and more important than larger zooplankton, while viral infections are suggested to be of less importance (reviewed in Vernet et al, 2019). Regarding total losses, a recent study partly concerning our study area and based on bio-optical observations from BGC-Argo floats, concluded that grazing (including viral lysis) was responsible for 83% of the losses on average and was by far more important than phytodetritus sinking (Moreau et al, 2020). In addition, grazing was found to be more important in the later part of the production season.…”
Section: Bloom Endmentioning
confidence: 88%
“…The percentages given represent approximate mean proportions of total primary production sequestered in the sea floor, broken down via the microbial loop and consumed by zooplankton and benthic consumers, based on several studies from high-productivity shelf environments and the wider literature (Azam, 1998;Ducklow et al, 2007;Hill et al, 2012;Garzio et al, 2013;Sailley et al, 2013;Ballerini et al, 2014;Murphy et al, 2016;Barnes, 2017). Murphy et al, 2016;Moreau et al, 2020). Consumption by benthic animals is the carbon fate characterised by the highest diversity (many animal phyla) and richness (tens of thousands of species), and has been estimated to account for up to 18% of primary production (Barnes, 2017).…”
Section: Fate Pathways Of Primary Productionmentioning
confidence: 99%
“…Autonomous in situ measurements will also allow for in-depth studies of the dynamics between phytoplankton and sea ice. While a few studies using floats already exist in marginal ice zones (e.g., Moreau et al, 2020;von Berg et al, 2020), further works would help reveal how phytoplankton changes with sea ice retreat at finer scales. Ocean color remote sensing, i.e., satellite-based measurements of visible light reflected off the upper ocean, will be essential toward studying the NAP ecosystem.…”
Section: Main Knowledge Gaps and Future Research Directionsmentioning
confidence: 99%